Some Reflections On How To Approach Chinese Culture - Li, Shi (Penerbit Universiti Sains Malaysia (USM Press), 2013)
With China being one of the largest sources of inbound tourists to Australia, the need to better understand Chinese culture has never been more highly emphasised by various organisations represented in Australian media, yet some cultural misreading with thinly-veiled value judgements are regularly discerned. Accordingly, a better cultural awareness is imperative for Australians to approach and understand Chinese people. This paper gives a brief review of the definitions of culture, its emergence and role in international relations. It then proceeds to the definition of Chinese culture and in particular, the turbulent history of modern Chinese culture. After a few preconceptions and misconceptions of Chinese culture in Australia are presented for discussion, finally some suggestions are made to help develop a historical and holistic view of Chinese culture.